Creatinine clearance and subclinical target organ damage in primary hypertension - Das, SK; Jha, SC (Journal of Institute of Medicine Nepal, 2011)
Introduction: Despite the widely recognized dangers of uncontrolled hypertension, the disease remains inadequately treated in the majority of patients. This may be, in large part, because of the asymptomatic nature of the disease for the first 15 to 20 years, even as it progressively damages the cardiovascular system. Therefore, assessment of hypertension related subclinical target-organ damage represents a key diagnostic procedure for the risk stratification of hypertensive patients. Methods: A prospective case control study of 40 cases (hypertensive patients with CCR<60) and 40 controls (hypertensive patients with CCR>60) was conducted in Tribhuvan University Teaching Hospital (TUTH). Renal function was estimated by the Cockcroft-Gault formula. Left ventricular hypertrophy was determined by echocardiography. Retinal vascular changes were evaluated by direct ophthalmoscopy. Microalbumin in urine was measured from spot morning sample. Results: The prevalence of Left ventricular hypertrophy (LVH), microalbuminuria and retinopathy in cases and control group was 55% VS 20% (P=.001), 50% VS 20% (P=.004) and 92.5% VS 52.5% (P=.001). Patients with microalbuminuria showed prevalence of LVH, CCR<60 and retinopathy as 78.57%, 71.43% and 100% respectively. There was high prevalence of grade I and grade II retinopathy in patients with low CCR Conclusions: Results show that a reduction in creatinine clearance and/or presence of microalbuminuria is a marker of subclinical organ damage in patients with primary hypertension and normal serum creatinine irrespective of BP load and other traditional risk factors. Keywords: Creatinine clearance; primary hypertension; subclinical; target organ damage. DOI: http://dx.doi.org/10.3126/joim.v32i3.4957 Journal of Institute of Medicine, December, 2010; 32:3 30-33